Fostering Industrial Competence: The Role of Vocational Sewing Training in Karawang - Santika, Tika (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This article explores the implementation of competency-based learning in the sewing training program at the Vocational Training Center in Karawang, aiming to enhance the effectiveness of skill acquisition among participants. The study employs a descriptive qualitative approach using a case study method. Data were collected through direct observation during training sessions, in-depth interviews with instructors and participants, and documentation of learning activities. The findings reveal that the competency-based approach has a positive impact on participants’ mastery of technical skills, fosters independent learning, and improves job readiness. Key success factors include a flexible curriculum, performance-based assessments, and the presence of competent instructors. These results highlight the effectiveness of competency-based training models in vocational education, particularly in the field of sewing.